Analisis Pengaruh Percepatan Pekerjaan Struktur dan Penundaan Pembayaran terhadap Cashflow Proyek Gedung X di Jawa Timur - Purwandari, Desi Ayu; Wiryasuta, I Ketut Hendra; Hardiyanti, Siska Aprilia; Safitri, Fikca Ayuk; Sandi, Enes Ariyanto (Politeknik Negeri Lhokseumawe, 2024)
Construction projects require complex resources. One resource that needs to be considered is the project cash flow aspect. If cash flow is not calculated properly, it will result in negative impacts, namely losses resulting in the project being stopped. In project implementation, acceleration is often carried out for certain purposes and payments are often delayed due to administrative negligence or non-compliance with contract provisions. This research aims to analyze the effect of accelerating structural work and delaying payments on the cash flow of the building x construction project in East Java. The method used for this research is to use cash flow analysis which consists of calculating cash in, cash out and overdraft. Cash flow calculations are carried out, namely calculating cash flow according to the contract, cash flow by accelerating structural work for 2, 4 and 6 weeks. Apart from that, cash flow is also calculated with payment delays of 1, 2 and 3 weeks. Based on the results of the analysis, the faster the project is implemented, the smaller the peak overdraft value will be and the final overdraft value will be greater. This will provide benefits to the contractor in terms of overdraft value because it provides smaller cash and produces greater profits. On the other hand, if the term payment experiences a longer delay, it will result in a larger peak overdraft value and a smaller final overdraft value. This will have a detrimental impact on contractors because they have to provide increasingly large cash reserves, but produce increasingly smaller profits.